1996
DOI: 10.1073/pnas.93.22.12159
|View full text |Cite
|
Sign up to set email alerts
|

A single G-to-C change causes human centromere TGGAA repeats to fold back into hairpins.

Abstract: Recently, we established that satellite III (TGGAA). tandem repeats, which occur at the centromeres of human chromosomes, pair with themselves to form an unusual "self-complementary" antiparallel duplex containing (GGA)2 motifs in which two unpaired guanines from opposite strands intercalate between sheared GoA base pairs. In separate studies, we have also established that the GCA triplet does not form bimolecular (GCA)2 motifs but instead promotes the formation of hairpins containing a GCA-turn motif in which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 31 publications
2
32
0
Order By: Relevance
“…By combining this information with our high-resolution structure of the dTGGAA repeat duplex, the structural basis of the molecular behavior observed in the smFRET experiments becomes clear. For sequences containing an odd number of dTGGAA repeats, the end-to-end configuration is optimal because it forms the highest number of duplex interactions while maintaining the 1-nt loop structure proposed by Zhu et al (11). In contrast, sequences containing an even number of dTGGAA repeats can either maintain the 1-nt loop structure and leave a dangling overhang or maintain the end-to-end configuration and form octaloop structures (Fig.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…By combining this information with our high-resolution structure of the dTGGAA repeat duplex, the structural basis of the molecular behavior observed in the smFRET experiments becomes clear. For sequences containing an odd number of dTGGAA repeats, the end-to-end configuration is optimal because it forms the highest number of duplex interactions while maintaining the 1-nt loop structure proposed by Zhu et al (11). In contrast, sequences containing an even number of dTGGAA repeats can either maintain the 1-nt loop structure and leave a dangling overhang or maintain the end-to-end configuration and form octaloop structures (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…Because dTGGAA repeat expansion is associated with the neurodegenerative disease SCA31 (13), understanding its structural and chemical bases of configuration slippage may also be important in a physiological context. It has been shown by NMR that dTGGAA tends to form a hairpin with a single G residue in the loop closed by a sheared G:A mismatch (11,20). Nucleic acids that contain 5′-GGA/AGG-5′ or 5′-GAAA/AAAG-5′ motifs can form antiparallel duplexes stabilized by unpaired purine bases that extend their stacking interactions until reaching the sheared G:A base pair.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While DNA sequences with three TGGAA repeats bracketed by a Watson-Crick G Á C pair exclusively form duplex structures with three (GGA) 2 intercalation motifs, changing the central G of such heptadecamers to C converts them completely to hairpins that contain a (GGA) 2 intercalation motif in the stem and a GCA-turn single-residue loop (Chou et al, 1996b;Zhu et al, 1996). This extraordinary hairpin-promoting capability of the (GCA) triplet may perhaps be used to fold back (TGGAA) tandem repeats and perhaps cause the condensation of human centromeres.…”
Section: Single-residue Loops Closed By Pu áPu Pairsmentioning
confidence: 99%
“…However, recent experiments have shown that sheared G ÁA base-pairing is an exception to this rule. The special geometry of sheared or side-by-side G Á A pairing has been found to be quite stable and compatible with¯anking WatsonCrick base-paired B-form DNA structure either as tandem base-pairs in (CGAG) 2 or (TGAA) 2 contexts (Li et al, 1991a,b;Chou et al, 1992aChou et al, ,b, 1994aCheng et al, 1992;Lane et al, 1992Lane et al, , 1994Katahira et al, 1993;Green et al, 1994), as base-pairs closing single-residue hairpin loops (Hirao et al, 1994;Zhu et al, 1995aZhu et al, , 1996Chou et al, 1996a,b), as basepairs closing two-residue hairpin loops (Hirao et al, 1989(Hirao et al, , 1990, as base-pairs bracketing unpaired purines (Chou et al, 1994b;Zhu et al, 1995bZhu et al, , 1996, or as base-pairs bracketing a single unpaired purine (our unpublished results). Due to their great potential in important biological functions such as DNA replication and centromere formation, we will describe structural characteristics of this type of basepairing and discuss its occurrence in the chromosomes of several single-stranded DNA viruses and in the centromere of human chromosomes.…”
Section: Introductionmentioning
confidence: 98%